2017
DOI: 10.1186/s12864-017-4050-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of LTR-retrotransposon diversity and its impact on the evolution of the genus Helianthus (L.)

Abstract: BackgroundGenome divergence by mobile elements activity and recombination is a continuous process that plays a key role in the evolution of species. Nevertheless, knowledge on retrotransposon-related variability among species belonging to the same genus is still limited. Considering the importance of the genus Helianthus, a model system for studying the ecological genetics of speciation and adaptation, we performed a comparative analysis of the repetitive genome fraction across ten species and one subspecies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 57 publications
2
45
0
1
Order By: Relevance
“…() and estimates for H. agrestis , H. carnosus and H. porteri were reported previously by Qiu & Ungerer (). All other GS estimates were newly generated for the current study, although independent estimates for some Helianthus species have been reported elsewhere (Sims & Price, ; Tetreault & Ungerer, ; Mascagni et al ., ). Newly reported estimates in the current study are based on an average of 3.57 accessions per species, with between one and 10 biological replicates assayed per accession (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…() and estimates for H. agrestis , H. carnosus and H. porteri were reported previously by Qiu & Ungerer (). All other GS estimates were newly generated for the current study, although independent estimates for some Helianthus species have been reported elsewhere (Sims & Price, ; Tetreault & Ungerer, ; Mascagni et al ., ). Newly reported estimates in the current study are based on an average of 3.57 accessions per species, with between one and 10 biological replicates assayed per accession (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…TEs, particularly longterminal repeat (LTR) retrotransposons, are also predominantly located in heterochromatic regions of the genome. In plants, LTR retrotransposons tend to be more abundant than non-LTR structural evolution of plant genomes (Flavell et al 1992;Voytas et al 1992;Mascagni et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These observations do not, however, address the extent to which TEs are expressed or mobilised in plant development during germination, much less the possible functional consequences of such activation. Clarifying these issues may afford a new mechanistic view of plant adaptation and evolution (Mascagni et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in higher plants, RLXs compose more than half of the repetitive DNA; they not only facilitate homologous recombination, but also can undergo intra-and inter-RLX recombination that is part of their dynamism [4,[8][9][10]. The RLXs are generally dispersed throughout genome, displaying relatively high structural diversity [11][12][13][14][15]. Retroelements have been suggested as an important creative force in genome evolution, driving processes such as mutation, recombination, genome expansion, and adaptation of an organism to changing environmental conditions [3,14,16].…”
Section: Introductionmentioning
confidence: 99%